Civil Liability Arising from the Marketing of a Hotel Trademark - Ghanim, Ahmed F.; Shakir, Anas I. (PROSPECTIVE RESEARCHES, 2025)
A trademark is a means of communication between its owner and the beneficiary of the service. Economic enterprises seek to promote their goods or services by using attractive means, represented by well-known and distinctive trademarks, to attract and engage the largest possible number of consumers and engage them with the service provided. This is achieved through various advertising media, such as radio, television, the press, publications, and posters placed on public roads. The importance of this research lies in the hotel trademark's critical importance in our current time, as it has become closely linked to our daily lives. Products, goods, and services all bear distinct trademarks that distinguish them from similar products, given its close connection to trade and the economy, and the competition between companies and organizations over trademarks. The research problem is highlighted by the following question: To what extent do civil provisions affect the protection of the marketing of hotel trademarks and the prevention of infringement?